Baricitinib Mitigates Methotrexate-Induced Liver Fibrosis Model via YAP Pathway - Mehmet Ulusan; Mumin Alper Erdogan; Ozkan Simsek; Zafer Dogan; Bertug Bekir Ciftci; Gultekin Atalan; Oytun Erbas (Medicina)
Background and Objectives: Liver fibrosis, a chronic process caused by various pathogenic factors, including drug toxicity, metabolic disorders, and chronic inflammation, is associated with liver-related mortality rates worldwide. It has been established that methotrexate (MTX), a pharmaceutical agent utilised in the treatment of numerous diseases, induces hepatic fibrosis. Currently, there is still a paucity of clinically efficacious antifibrotic drugs for the management of hepatic fibrosis. Thus, the present research sought to evaluate the antifibrotic effects of baricitinib in a rat model of MTX-induced liver fibrosis through the yes-associated protein (YAP) pathway. Materials and Methods: A total of 36 Wistar rats were assigned to three groups (n = 12) randomly: a control group, an MTX-induced liver fibrosis group, and a baricitinib-treated group, which received 20 mg/kg/day of baricitinib following fibrosis induction. All treatments were administered for 10 days. Results: Biochemical analyses revealed significant increases in plasma alanine aminotransferase (ALT), cytokeratin-18 (CK-18), and malondialdehyde (MDA) levels, as well as liver transforming growth factor-beta (TGF-β), YAP1, and MDA levels, in the MTX-induced fibrosis group in comparison to the control group (p < 0.05). Notably, baricitinib addition significantly reduced these biomarkers (p < 0.05). A histopathological evaluation further confirmed a marked reduction in fibrosis, hepatic necrosis, and cellular infiltration in the baricitinib-treated group relative to the MTX-induced fibrosis group. Conclusions: Accordingly, our findings suggest that baricitinib mitigates MTX-induced liver fibrosis, potentially through its anti-inflammatory and antifibrotic effects mediated by the suppression of the YAP signalling pathway. These results highlight that baricitinib could be a potential treatment option for patients with liver fibrosis.